Product Development using Rattan as an Alternative Material in Padang West Sumatera - Ovi Lestari; Nanang Fatchurrohman; Mohammad Farid; Mutiara Yetrina; Ismayuzri Bin Ishak (Takaza Innovatix Labs Ltd., 2025)
This investigation involved micro, small and medium enterprises (MSMES) engaged in home furniture manufacturing services. The conventional method used by these craftsmen usually uses tools that are easily available around us, using a woven or plaited system. Commonly used materials include Manau, bamboo, ropes and nails. This work is also said to pose a risk, because rattan, if it has been scraped or thinned to make it flexible, can endanger the craftsman. However, there are complaints from craftsmen who say that nowadays not many people want to use furniture made from handicrafts or from natural materials. People who have used a lot of home furniture made from various materials such as plastic, glass and others. In making this craft, a heating system is also used to heat the Manau with fire so that it can be easily bent to form parts of the craft framework.